Formulasi Kebijakan Publik Pengarusutamaan Gender di Kabupaten Magelang: Analisis Proses Penyusunan Peraturan Daerah Nomor 1 Tahun 2024 - Khoirunnisa, Khoirunnisa; Tri Nugraha, Joko; Boedi Orbawati, Eny; Ivan Adi Kristianto, Yohanes (PUBLICNESS: Journal of Public Administration Studies, 2025)
This study aims to analyze the drafting process of the Regional Regulation on Gender Mainstreaming No. 1 of 2024 in Magelang Regency, which reflects the government's effort to address gender inequality. Using a qualitative approach with interviews, documentation, and observation, the research applies Thomas R. Dye’s policy formulation theory, encompassing stages of problem identification, agenda setting, formulation, ratification, implementation, and evaluation. All stages were followed in drafting the regulation. The Social Service initiated problem identification, which the Regent then forwarded to the DPRD as an executive draft. Agenda setting occurred through the formation of a special committee and preparation of academic papers. The formulation process took place in three committee meetings. The regulation was swiftly ratified through a plenary session, signed by the governor, and legally enacted on January 26, 2026. Implementation involved socialization and public campaigns by the Social Service, while evaluation was carried out with BPS and legislative oversight. A key finding is the critical role of intensive socialization to ensure the regulation effectively reaches and impacts its target audience.